Virtual screening of thieno[3,2-b]pyridine arylthioether (hetero)aryltriazole derivatives as potential tyrosine kinase VEGFR2 inhibitors. - Calhelha, Ricardo C. (2014)
Recently we presented a series of thieno[3,2-d]pyrimidinc ether I ,3-diaryl ureas with potent VEGFR2 inhibit ion activity. The binding mode was analyzed and the compounds showed a type-11 tyrosine kinase inhibition mode, with the thienopyrimidine moiety forming a Hydrogen Bond (H-bond) with CYS919 residue and the urea moiety forming a H-bonds with key residues G LU885 and ASP I 046 of the kinase domain. In this study, the potential of changing the more widely used urea moiety to a triazole moiety now in thieno[3,2-b)pyridine a rylthioethers, was analyzed. A number of 3D thieno[3.2-b ]pyrid ine arylthioethers (hetero )aryltriazole derivatives (Figure I) were designed and then molecular docking studies, using AutoDock4, were performed against a VEGFR2 crystal.